Biodegradation of o-Benzyl-p-Chlorophenol - Swisher, R. D. (1973)
The extent of biodegradation of o-benzyl-p-chlorophenol, marketed as a germicide under the name Santophen(®) 1 (Monsanto Co.), in river water, sewage, and activated sludge was determined. Biodegradation was assessed by use of a colorimetric procedure for phenolic materials, carbon analysis, and CO(2) evolution. In unacclimated river water, 0.1 mg of Santophen 1 per liter was degraded within 6 days. In sewage, 0.5 and 1.0 mg/liter levels of Santophen 1 were degraded in 1 day. Acclimated activated sludge achieved 80% biodegradation of 1.0 mg/liter Santophen 1 in 8 h and 100% in 24 h. When effluent from a semicontinuous activated sludge unit, acclimated to 20 mg of Santophen 1 per liter was used as the inoculum for the CO(2) evolution procedure, 60% of the total theoretical CO(2) was evolved from Santophen 1. Based on the results of these studies, indicating Santophen 1 to be readily biodegraded in at least four biological systems, the continued use of present levels of Santophen 1 should present no significant environmental problems.